Relación entre el nivel de cumplimiento de las buenas prácticas de dispensación (bpd) y la satisfacción percibida por el usuario externo atendido en la farmacia de emergencia del Hospital Belén de Trujillo, julio – diciembre del 2016 - Tandaypan Cruz, Noé Marcos (2017)
The present study aims to determine if there is a relationship between compliance with Good Practices of Dispensation (BPD) and satisfaction with the external User attended at the emergency pharmacy of Hospital Belén de Trujillo, 2016. The sample was made up of 92 users In this establishment and 7 pharmaceutical professionals working in emergency pharmacy of the Hospital Belén de Trujillo. To obtain the data, two surveys were carried out: a 15 - item survey for external users and a 30 - item questionnaire for pharmaceutical professionals relating them through the Spearman correlation coefficient (r) as well as the Chi - square test ( X2) with a 95% confidence interval and p value <0,005. Of the obtained results was obtained, 57,61% of the external users were satisfied while 16,30% were dissatisfied, from the surveys of the pharmaceutical professionals it was obtained that 71,43% comply with the Good Practices of Dispensing (BPD), while 28,57% did not meet. The relationship between Good Dispensation Practices (BPD) and user satisfaction through the X2Calculated Test = 18,61; indicating that there is a relationship